Social and Economic Factors Determining the Unemployment Rate in the Bregasmalang Region 2010-2020 - Rima Eka Kurnia; Yustirania Septiani (EKO-REGIONAL, 2021)
The research objective was to analyze the social and economic factors that affect unemployment in the development area of Central Java, namely in Brebes Regency, Tegal City, Tegal Regency, and Pemalang Regency (BREGASMALANG) in 2010-2020. The determinants of unemployment used in this study include the human development index, district/city minimum wage, and gross regional domestic product. The data used in this study are secondary data obtained from the Central Statistics Agency (BPS). The research method used in Panel Data Regression Analysis with Fixed Effect Model (FEM). The result of this study indicates that the human development index & district/city minimum wage it means that it has no significant effect on the open unemployment rate in Bregasmalang. Meanwhile, the gross regional domestic product has a negative and significant effect on the open unemployment rate in Bregasmalang. With the influence of regional gross domestic product on the open unemployment rate, therefore the government is expected to be able to maximize the sub-sectors contained in the GRDP so that the sub-sector is able to increase employment so that it can suppress the high unemployment rate in the Regency/City concerned, namely the Brebes Regency, Tegal City, Tegal Regency, and Pemalang Regency.Keywords: Open Unemployment Rate, HDI, District/City Minimum Wages, and GRDP